INTERAKSI SINERGIS DALAM KONSORSIUM TERMOFILIK: MENYEIMBANGKAN RASIO KONSENTRASI MIKROBA DALAM PRODUKSI BIOELEKTRIK - Alfatimah Azzahra, Balkis; Irdawati; Handayani, Dezi; Hilda Putri, Dwi (Universitas Cokroaminoto Palopo, 2025)
The global urgency for sustainable energy solutions amid climate change and fossil fuel depletion has driven innovation in Microbial Fuel Cells (MFCs). This study investigates the synergistic interactions within a thermophilic microbial consortium (MS9 & MS12) to optimize energy efficiency in MFCs. By varying the inoculum ratios (1:1, 1:2, and 1:3), the research evaluates how microbial population balance impacts bioelectricity production. The MFCs were operated for 24 hours, with voltage measurements recorded every 2 hours. Results revealed that a 1:3 (MS9:MS12) ratio achieved the highest voltage output, peaking at 20 hours before declining, indicating metabolic synergy and efficient substrate utilization. Descriptive analysis highlighted the critical role of cross-feeding mechanisms and functional complementarity between species in enhancing electron transfer. The findings align with modular co-cultivation principles, emphasizing the importance of engineered microbial ratios for stable system performance. This study provides a protocol for designing balanced thermophilic consortia, advancing sustainable bioenergy strategies through optimized microbial interactions.